Frequency of Proximal Migration of Urinary Stone during Ureteroscopic Pneumonic Lithotripsy in KPK (Medical Forum Monthly, 2021)
Objective: To Study the Frequency of Proximal Migration of Urinary Stone During Ureteroscopic Pneumonic Lithotripsy.Study Design: Descriptive Cross Sectional Experimental StudyPlace and Duration of Study: This study was conducted at the department of Urology Lady Reading Hospital Peshawar, Nawaz Shareef kidney hospital swat, DHQ teaching hospital Sawabi, Women medical college Abbottabad from January, 2019 to May, 2020.Materials and Methods: Sample size was calculated using WHO calculator and total 160 patients were enrolled with 5% margin of error and 95% confidence interval and consecutive nonprobability sampling technique was used. All patients having urinary stone of size less than or equal to fifteen millimeters, age thirty to seventy years and male and female were included in the study whereas all those who had previous history of Extracorporeal shock wave lithotripsy, DJ stent placement, age less than 30 and > 70 were excluded from the study.After ethical committee permission from of the hospital, patients were admitted in the department and informed consent was taken. Data was recorded on a predesigned profarma and was analyzed using the statistical program SPSS version 20. Descriptive statistics like mean ± standard deviation was calculated for numerical variable age and size of stone.Results: During the study period 160 cases (83 males and 77 female) of ureteric stones were included in the study. In total 20 (12.5%) patients proximal stone migration was observed.Conclusion: It was estimated from study that proximal stone migration during pneumatic lithotripsy was major complication